The Efficacy of Lactocare® Synbiotic on the Clinical Symptoms in Patients with Psoriasis: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial. (7th October 2022) - Akbarzadeh, Ali; Alirezaei, Pedram; Doosti-Irani, Amin; Mehrpooya, Maryam; Nouri, Fatemeh
Abstract : Background . Attention to the administration of probiotics for the treatment of psoriasis has recently increased. Aim . In the present study, improvements in dermatology life quality index (DLQI), psoriasis area severity index (PASI), and visual analogue scale (VAS) scores in the psoriasis patients receiving Lactocare® probiotic were compared to psoriasis patients receiving placebo. Methods . A total of 52 psoriasis patients were included in this study and randomly divided into treatment and placebo (control) groups. The control group received topical hydrocortisone associated with placebo; in the treatment group, Lactocare® was administrated orally associated with hydrocortisone. The mean of VAS, DLQI, and PSAI scores was recorded and evaluated pretreatment and post-treatment in both groups for 3 months. The mean of the scores in the control groups was compared to the treatment group. Intragroup analysis was preformed with a comparison of the mean of these scores at baseline 4-, 8-, and 12-weeks post-treatment. Results . In the treatment group, a significant decrease was seen in PASI, VAS, and DLQI scores compared to the control group on week 12 post-treatment. Conclusion . Oral administration of Lactocare® probiotic (two times daily) associated with administration of topical hydrocortisone resulted in the improvement of PASI, DLQI, and VAS scores in the patients with psoriasis after 12 weeks of treatment. PASI reduction occurred in all patients who received probiotics.